Influencia del carisma de Mercedes de Jesús, en los jóvenes de tres obras educativas de la congregación Marianita - Castillo Palacios, Yeni Marilú (2015)
The purpose of this research is to know the degree of influence of the charisma of Mercedes de Jesus Molina and Ayala, in the students of Guaranda, Loja and Guayaquil. In the first chapter refers to the concept of charisma: its Biblical roots which contrasts with the sense which has been given in the sociology; the origen and evolution; It explores, on the origins of life religious of the charisma of the founders/ACE. The second chapter, deepen the charisma of the Congregation "Mariana de Jesús", the life and spirituality of its founder, Jesús Mercedes Molina and Ayala the way that charisma has adapted within the social context. It continues to investigate the socio-cultural context of young people; lifestyles of so them called 'youth tribes'; a brief description of Marianita youth population of the three investigated works, that a survey of 20 questions opens divide in two blocks was applied to them: 1-10, explored the world of l... Youth, cultural elements, their values, their circle of friends and as these influence their behavior and identity, look for the opinion of young people on the values that are being transmitted by the Congregation of the Marianitas 11 to 20. In the third chapter are classified and analyzed the responses obtained, through a detailed analysis of the impact of education Marianita in the experience of values in students. In the chapter four are the conclusions and recommendations, you will reach the conclusion that there are three groups of students, with their respective sub-divisions and the degree of influence of the charisma of the founder of the values conveyed by the nuns and teachers from the Congregation, need to be improved and clarified.